Unconventional Monetary Policy in a Small Open Economy - MacDonald, Margaux; Popiel, Micha, Ksawery (Washington, D.C. : International Monetary Fund, 2017)
This paper investigates the effects of unconventional monetary policy in a small open economy. Using recently proposed shadow interest rates to capture unconventional monetary policy at the zero lower bound (ZLB) we estimate a Bayesian structural vector autoregressive model for Canada - a useful case where foreign shocks can be proxied by U.S. variables alone. We find that, during the ZLB period, Canadian unconventional monetary policy increased output (measured by industrial production) by 0.013 percent per month on average while US unconventional monetary policy raised Canadian output by 0.127 percent per month on average. Our results demonstrate the effectiveness of domestic unconventional monetary policy and the strong positive spillover effects that foreign unconventional monetary policies can have in a small open economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet